TIPE-TIPE SUPERVISI PENDIDIKAN - Salsabila Sisda Elzahra; M Satrio Rofi Fadhil; Subandi Subandi (CV. ALIM'SPUBLISHING, 2025)
This article discusses various types of supervision in Islamic education, which aim to improve the quality of teaching and learning. Supervision in Islamic education focuses not only on academic aspects, but also on the development of students' character and spirituality. The types of supervision discussed include administrative supervision, pedagogical supervision, and spiritual supervision. By providing concrete examples of practices in Islamic schools, this article shows how each type of supervision can be applied effectively to achieve holistic educational goals.types of supervisors often found in the environment. By identifying the characteristics of each type, readers are expected to understand the important role of supervisors in improving team performance. Through an analysis of concrete news related to supervisor behavior, this article also evaluates spelling errors that often appear in official communication, and provides recommendations for improvement. This study aims to raise awareness of the importance of effective communication